2011
DOI: 10.1007/s11113-011-9208-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Change, Risky Sexual Behavior, and the HIV/AIDS Pandemic: Linkages Through Livelihoods in Rural Haiti

Abstract: Local natural resources are central to rural livelihoods across much of the developing world. Such “natural capital” represents one of several types of assets available to households as they craft livelihood strategies. In order to explore the potential for environmental scarcity and change to contribute to perpetuation of the HIV/AIDS pandemic, we examine the association between declining natural capital and engaging in risky sexual behaviors, as potentially another livelihood strategy. Such association has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Four out of five Haitians are unemployed (World Bank 2006), and the absence of steady employment opportunities leave women (and men) searching constantly for new economic opportunities (Farmer, Léandre, Mukherjee, Claude, Nevil, Smith-Fawzi, Koenig, Castro, Becerra, and Sachs 2001). In rural areas, most women work in the agricultural sector (Charmes 2000); however, the country’s large-scale environmental degradation continuously threatens agricultural output (Hunter, Reid-Hresko, and Dickinson 2011). Thus, many rural women migrate to other rural communities where superior cultivation opportunities are available or to Haiti’s urban centers in search of employment in petty trade, industry, or domestic work (Ahlers 1978).…”
mentioning
confidence: 99%
“…Four out of five Haitians are unemployed (World Bank 2006), and the absence of steady employment opportunities leave women (and men) searching constantly for new economic opportunities (Farmer, Léandre, Mukherjee, Claude, Nevil, Smith-Fawzi, Koenig, Castro, Becerra, and Sachs 2001). In rural areas, most women work in the agricultural sector (Charmes 2000); however, the country’s large-scale environmental degradation continuously threatens agricultural output (Hunter, Reid-Hresko, and Dickinson 2011). Thus, many rural women migrate to other rural communities where superior cultivation opportunities are available or to Haiti’s urban centers in search of employment in petty trade, industry, or domestic work (Ahlers 1978).…”
mentioning
confidence: 99%
“…In Nigeria, a study also found that attempts to mitigate food deprivation partly explained slum adolescent girls’ engaging in risky sexual behaviors [77]. The observation that men have more non-sexual opportunities to earn income has been documented in Mozambique and Haiti [28, 78], and was also described among our youth in Kenya. There has been some evidence as well suggesting that young men in Lesotho increased demand for sex partners once obtaining employment or income [76], and that economic hardship for Zimbabwean men diminished their capacity to support sexual relationships [79].…”
Section: Discussionmentioning
confidence: 61%
“…In sub-Saharan Africa, fish-for-sex has garnered particular attention largely because of exceptionally high prevalence of HIV around inland lakes, including Lake Victoria (Béné & Merten, 2008;Kwena, Camlin, Shisanya, Mwanzo, & Bukusi, 2013;MacPherson et al, 2012). More broadly, a burgeoning literature seeks to link HIV to environmental change (Fiorella, 2013;Hunter, Reid-Hresko, & Dickinson, 2011;Mojola, 2011;Talman, Bolton, & Walson, 2013).…”
Section: Background (A) Lake Victoria Fisheries and Gendermentioning
confidence: 99%